Criminal Law Enforcement in the Military Againts Same-sexual Assault Perpertators Within the National Armed Forces (Decision Number 67K/Mil2021) - Hari, Tour Dini; Purwoto, Ady; Ferrary, Ande Aditya Iman (JURNAL MAHASISWA YUSTISI, 2025)
Military criminal Law plays an important role in maintaining discipline, moralty, and honor within the Indonesia National Armed Forces (TNI). One of the serious Violations of concern is acts of sexual misconduct, including same-sexual misconduct. The handling of such cases involves not only legal aspects but also ethical values and military discipline. This study analyzes how military criminal law, particular within the scope of the Military Penal Code (KUHPM) and Law Number 25 0f 2014 on Military Disciplen law, regulates and prosecutes perprtrators of same-sexsual misconduct within the TNI. The research method used is normative juridical with a qualitative approach to relevant cases. The findings indicate that akthough legal provisions are already in place, law enforcement still faces obstacles, both due to the closed nature of military culture and the lack of protection for victims. Therefore, there is a need to raise awareness among TNI members to create a more professional military environment and to uphold the good name of the Indonesia National Armed Forces